Multilevel medical insurance mitigate health cost inequality due to air pollution: Evidence from China - Ennan Wang; Minglai Zhu; Yisha Lin; Xiaoyu Xi (BMC, 2024)
Abstract Background Air pollution affects residents' health to varying extents according to differences in socioeconomic status. However, there has been a lack of research on whether air pollution contributes to unfair health costs. Methods In this research, data from the China Labour Force Dynamics Survey are matched with data on PM2.5 average concentration and precipitation, and the influence of air pollution on the health expenditures of residents is analysed with econometric methods involving a two-part model, instrument variables and moderating effects. Results The findings reveal that air pollution significantly impacts Chinese residents' health costs and leads to low-income people face health inequality. Specifcally, the empirical evidence shows that air pollution has no significant influence on the probability of residents' health costs (β = 0.021, p = 0.770) but that it increases the amount of residents' total outpatient costs (β = 0.379, p < 0.006), reimbursed outpatient cost (β = 0.453, p < 0.044) and out-of-pocket outpatient cost (β = 0.362, p < 0.048). The heterogeneity analysis of income indicates that low-income people face inequality due to health cost inflation caused by air pollution, their total and out-of-pocket outpatient cost significantly increase with PM2.5 (β = 0.417, p = 0.013; β = 0.491, p = 0.020). Further analysis reveals that social basic medical insurance does not have a remarkable positive moderating effect on the influence of air pollution on individual health inflation (β = 0.021, p = 0.292), but supplementary medical insurance for employees could reduce the effect of air pollution on low-income residents' reimbursed and out-of-pocket outpatient cost (β=-1.331, p = 0.096; β=-2.211, p = 0.014). Conclusion The study concludes that air pollution increases the amount of Chinese residents' outpatient cost and has no significant effect on the incidence of outpatient cost. However, air pollution has more significant impact on the low-income residents than the high-income residents, which indicates that air pollution leads to the inequity of medical cost. Additionally, the supplementary medical insurance reduces the inequity of medical cost caused by air pollution for the low-income employees.